Inflammation and lymphocyte infiltration are associated with shorter survival in patients with high-grade glioma. (1st January 2020) - Marinari, Eliana; Allard, Mathilde; Gustave, Robin; Widmer, Valérie; Philippin, Géraldine; Merkler, Doron; Tsantoulis, Petros; Dutoit, Valérie; Dietrich, Pierre-Yves
ABSTRACT: Glioma represents a serious health burden in terms of morbidity and mortality. The prognostic significance of the lymphoid and myeloid infiltrates in glioma is not clearly determined. Moreover, the characterization of different leukocyte subsets in the tumor microenvironment relies mainly on immunohistochemistry observations, and data about their association with prognosis are contradictory. Here, we performed acomprehensive study of both the tumor-infiltrating and circulating immune compartments of patients with high-grade glioma. Nineteen tumor biopsies and 30 PBMC samples were analyzed by RNA sequencing. Validation was performed on The Cancer Genome Atlas (TCGA) RNA sequencing data from glioma and on additional 39 tumor biopsies analyzed by flow cytometry. We identified prognostic tumor and peripheral immune signatures, which associate increased inflammation, immune infiltration and activation with shorter overall survival in high-grade glioma patients. Importantly, we confirmed our observations by flow cytometry analysis and validated the tumor-signature using the TCGA dataset. In addition, both tumor genotype and grade associated with the degree of glioma immune infiltration. Unlike in the majority of cancers, lymphocyte infiltration at the tumor site is anegative prognostic factor in glioma, suggesting the ambivalent pro-tumorigenic role of immune responses in glioma.